P62 A discrete choice experiment (DCE) to quantify the influence of trial features on the decision to participate in Cystic Fibrosis (CF) trials. (11th November 2022) - Dobra, RA; Davies, JC; Elborn, JS; Kee, F; Madge, S; Boeri, M
Abstract : Background: Patient-centred trial designs improve research quality and efficiency, ultimately allowing safe drugs to reach clinic more quickly. Our qualitative work suggests quantifying 6 key trial attributes could define priorities for patient-centred CF trials: type of medicine, trial design (placebo v open label), washout, stipend, location of visits, and post-trial drug access. Method: Preferences were determined using an online discrete choice experiment. DCEs use experimental design to systematically investigate the value participants place on multiple predefined features when making complex decisions. pwCF age 16+ were recruited through social media. Respondents considered 12 scenarios, choosing between 2 hypothetical trials (or 'no trial' ) characterised by attribute levels based on current CF trials. Attributes and levels were combined using efficient experimental design. The cross-sectional data were explored using a Random Parameters Logit model. Responses: Oct2020-Jan2021, n= 207. Never participated in a trial: 57%. Attributes are discussed in order of importance. (1) The strongest influence on the decision to participate was location of visits, pwCF favouring their usual centre and being less likely to participate the greater the travel distance. (2) Post-trial drug access ranked next. pwCF are less likely to take part if they do not gain access to the drug on completion. Open-Label extension phases or Managed Access Programmes were similarly persuasive in decisions to participate. Priority access to later trials did not encourage participation. (3) With regards to medicine type pwCF favoured trials of CFTR modulators over other drugs, with no strong preference between antibiotics & anti-inflammatories. (4) A larger stipend was associated with greater willingness to participate, to a maximum value of £70. (5) pwCF did not favour a washout period but were more prepared to washout non-modulators than modulators. (6) There was minimal difference in intention to take part in placebo vs open-label trials. There was a complex interaction between placebos and washouts. Subgroup data will be presented. Conclusions: We identified factors that are most important to pwCF when deciding whether to join a trial. The European Cystic Fibrosis Society have agreed to incorporate our findings into their review process, meaning our study may realistically inform patient-centred trial design with benefits to recruitment and retention.